126 | | |
127 | | |
128 | | Now in the limit where we ignore spatial derivatives in density and magnetic field orientation, we can throw away the C terms - and if we also assume backward Euler, we can set |
129 | | |
130 | | $\psi=1$ |
131 | | |
132 | | $\phi' = \frac{-\lambda}{\lambda+1}$ |
133 | | |
134 | | $E_{ij}=\kappa_\parallel n b_i b_j$ |
135 | | |
136 | | |
137 | | If we are using Crank-Nicholson, then |
138 | | |
139 | | $\psi=1/2$ |
140 | | |
141 | | $\phi' = \frac{1-\lambda}{\lambda+1}$ |
142 | | |
143 | | $E_{ij}=\frac{1}{2}\kappa_\parallel n b_i b_j$ |
144 | | |
145 | | |
146 | | |
147 | | Now for the perpendicular term, we have |
148 | | |
149 | | $\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \frac{-n \kappa_\perp}{B^2 \left (\Lambda+1\right )} \left ( \hat{b} \cdot \nabla T_*^{\Lambda+1} \right ) + n \frac{n \kappa_\perp}{B^2 \left (\Lambda+1\right )}\nabla T_*^{\Lambda+1} \right ]$ |
150 | | |
151 | | And performing a Taylor expansion gives |
152 | | |
153 | | $\frac{\partial T}{\partial t} = \nabla \cdot \left [ -n \hat{b} \frac{n \kappa_\perp}{B^2 \left ( \Lambda+1 \right ) } \left ( \hat{b} \cdot \nabla \left ( -\Lambda T^{\Lambda+1} + \left ( \Lambda + 1 \right ) T^{\Lambda}T_{*} \right ) \right ) + n \frac{n \kappa_\perp}{B^2 \left ( \Lambda+1 \right ) } \nabla \left ( - \Lambda T^{ \Lambda+1} + \left ( \Lambda + 1 \right ) T^{\Lambda} T_{*} \right ) \right ] $ |
154 | | |
155 | | And in Einstein notation gives |
156 | | |
157 | | $\partial_t T = - \partial_i n b_i \frac{n \kappa_\perp}{B^2 \left ( \Lambda+1 \right ) } b_j \partial_j \left ( -\Lambda T^{\Lambda+1} + \left ( \Lambda + 1 \right ) T^{\Lambda}T_{*} \right ) + \partial_i n \frac{n \kappa_\perp}{B^2 \left ( \Lambda+1 \right ) } \partial_i \left ( - \Lambda T^{ \Lambda+1} + \left ( \Lambda + 1 \right ) T^{\Lambda} T_{*} \right ) $ |
158 | | |
159 | | |
160 | | The first term is very similar to the parallel case - and the second term can be made similar by replacing $b_i b_j$ with $\delta_{ij}$ |
161 | | |
162 | | $\phi' = \frac{\phi-\psi \Lambda}{\psi \left ( \Lambda + 1 \right )}$ |
163 | | |
164 | | $B_j = \phi' C_j $ |
165 | | |
166 | | $C_j = -\kappa_\perp \psi \partial_i n^2 B^{-2} \left ( b_i b_j - \delta_{ij} \right ) $ |
167 | | |
168 | | $D_{ij}=\phi'E_{ij}$ |
169 | | |
170 | | $E_{ij} = -\kappa_\perp \psi n^2 B^{-2} \left ( b_i b_j - \delta_{ij} \right ) $ |